Assistive technology and the narrative writing of a student with a learning disability - Ongtengco, Maria Hazelle Preclaro (2010)
This article focuses on how assistive technology devices, specifically the use of a word processor equipped with word prediction and text-to-speech software, have changed the narrative output of a seventh grader who has been diagnosed to have a learning disability. A pre-writing tool was needed to serve as a guidepost for composing. Positive effects on spelling performance and legibility of written work, but less on content, were observed.
Keywords: Self-help devices for people with disabilities; Learning disabilities; Educational technology